Factor Determinants on Availability and Consumption of Rubberwood in Peninsular Malaysia (Journal of Tropical Resources and Sustainable Science (JTRSS), 2015)
Rubberwood sawntimber has become one of the major contributors to the Malaysian furniture export and economic growth in the past two decades as its demand from wooden furniture manufacturing has increased tremendously. Factors affecting availability and consumption of rubberwood sawntimber are identified through the multiple regression models. The results of the regression analyses have been statistically diagnosed and modified to generate the best models. Availability of rubberwood sawntimber is influenced by replanted area, price of rubberwood log, latex price and previous production of rubberwood sawntimber. Consumption of rubberwood sawntimber is influenced by national income and prices of other light hardwood species that are mainly consumed by sawmills, i.e. Dark Red Meranti and Red Meranti. The findings could be used as a guideline for the policy maker to develop strategies for further strengthens the wood based industry as a whole.
Keywords: Rubberwood; wooden furniture manufacturing; regression analyses; availability; consumption